ANALISIS USAHA TAMBAK GARAM DI DESA GEDONGMULYO KECAMATAN LASEM KABUPATEN REMBANG - Ragil P. Andriyano; Suadi Suadi; Supardjo S. Djasmani (Universitas Gadjah Mada, 2013)
The purpose of this study was to determine the cost structure dan income of traditional salt farming at Gedongmulyo Village, Sub District of Lasem, Rembang. All salt farmers, account for 30 owners were selected as respondents and interviewed. The study indicated that respondents have varied farm land ranging from 750 m2 to 220,000 m2. The cost and revenue analysis were using farm land that was converted into one hectare per year. The total cost of salt farming was counted for Rp. 35,267,668 which mostly allocated for labor cost, account for Rp. 20,894,631 (59,24%). The total revenue of the business was Rp. 53,076,281 per hectare, comprises of revenue from salt production, amount of Rp. 41,308,681 and milkﬁ sh production account for Rp. 11,767,600. Therefore, farmer income was calculated at Rp. 17,808,613 per hectare. The study also indicated that R/C ratio was 1.50, which means that the business was worth to be developed and expanded. Nevertheless, there were few challenges, including the issue on climate variability, salt market and marketing, and business management. Appropriate policies and supporting programs are need to ensure the sustainability of the people business.